2003
DOI: 10.1590/s0066-782x2003001000004
|View full text |Cite
|
Sign up to set email alerts
|

Initial diagnostic errors in children suspected of having heart disease: prevalence and long-term consequences

Abstract: A global analysis demonstrated that diagnostic error in the initial evaluation of children with cardiac murmurs is real, reaching approximately 6% of cases. The majority of these misdiagnoses were in patients with an initial diagnosis of cardiopathy, which was not confirmed through later complementary examinations. Clinical cardiovascular examination is an excellent resource in the evaluation of children suspected of having cardiopathy. Immediate outpatient discharge of children with an initial diagnosis of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…8 However, until 15 years ago, this operation was associated with higher mortality and morbidity including complete heart block, thrombosis, and stroke. 3,5 In recent years, with improved surgical techniques, cardiopulmonary bypass methods, newer mechanical valves, and tissue derived bioprosthetic valves, increasing number of young children with early-onset MFS are surviving mitral valve replacement surgeries, as noted in our cohort. Indications for mitral valve replacement following established guidelines include symptomatic mitral regurgitation, or asymptomatic patients with one or more of the following features: severe left ventricular enlargement with end systolic diameter of the left ventricle exceeding 4 cm, left ventricular systolic dysfunction, secondary pulmonary hypertension, or development of new onset atrial fibrillation.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…8 However, until 15 years ago, this operation was associated with higher mortality and morbidity including complete heart block, thrombosis, and stroke. 3,5 In recent years, with improved surgical techniques, cardiopulmonary bypass methods, newer mechanical valves, and tissue derived bioprosthetic valves, increasing number of young children with early-onset MFS are surviving mitral valve replacement surgeries, as noted in our cohort. Indications for mitral valve replacement following established guidelines include symptomatic mitral regurgitation, or asymptomatic patients with one or more of the following features: severe left ventricular enlargement with end systolic diameter of the left ventricle exceeding 4 cm, left ventricular systolic dysfunction, secondary pulmonary hypertension, or development of new onset atrial fibrillation.…”
Section: Discussionmentioning
confidence: 67%
“…Unlike classical MFS, where death is often due to acute aortic dissection and rupture, patients with this early-onset form die from congestive heart failure (CHF) secondary to severe cardiac valvar insufficiency. [3][4][5] The rarity of this disease coupled with a high mortality during early childhood makes the prognosis and disease progression difficult to predict. 6,7 We report three patients with early-onset or infantile MFS, whose clinical evolution has been remarkably positive, when compared with other reported cases in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…14 In paediatric cardiology, diagnostic errors have been reported in a wide range of clinical settings and domains, including in-hospital and ambulatory settings, echocardiography, and paediatric and neonatal ICUs. 12,[15][16][17][18][19][20][21][22][23][24] Diagnostic errors may contribute significantly to poor outcomes in patients with critical CHD. Goldstein et al reported that diagnostic errors occur more frequently in children who die in the ICU compared with those who die in the emergency department or general ward.…”
mentioning
confidence: 99%